Pengelolaan Dana Punia Melalui Pengembangan Pendidikan Pasraman Dan Pemberdayaan Ekonomi Umat di Badan Dharma Dana Punia Raman Utara - Antara, Dewa Putu; Tanaya, I Nyoman Tri Bayu (Kamaya: Jurnal Ilmu Agama, 2024)
Dana punia is a sacred activity as one of the implementations of the teachings of dharma. The purpose of this study is to determine the management system of Punia Funds through the development of pasraman education and empowerment of the people's economy carried out by BDDPRU and to determine the supporting and inhibiting factors for the development of Punia Funds for pasraman education and empowerment of the people's economy carried out by BDDPRU. With that, it will be possible to obtain a maximum fund management system by pasraman. In addition, this study is able to encourage and empower Hindus in the future. This research method is Qualitative and uses studies in accordance with Humanistic theory and the theory of Motivation to do business in the management of Dharma Dana. One of the supporting factors for BDDPRU is the existence of permanent punia funders, this supporting factor can provide a strong solution in the process of managing punia funds through the development of pasraman education and empowerment of the people's economy. One of the inhibiting factors is the lack of adequate facilities and infrastructure. In conclusion, the BDDPRU Punia Fund management system has used POAC (Planning, Organizing, Actuating and Controlling) management but has not been maximized.